Analysis of phenolic compounds from different morphological parts of Helichrysum devium by liquid chromatography with on-line UV and electrospray ionization mass spectrometric detection - Gouveia, Sandra C. (2021)
A simple and rapid method has been used for the screening and identification of the main phenolic compounds from Helichrysum devium using high-performance liquid chromatography with on-line UV and electrospray ionization mass spectrometric detection (LC-DAD/ESI-MS(n)). The total aerial parts and different morphological parts of the plant, namely leaves, flowers and stems, were analyzed separately. A total of 34 compounds present in the methanolic extract from Helichrysum devium were identified or tentatively characterized based on their UV and mass spectra and retention times. Three of these compounds were positively identified by comparison with reference standards. The phenolic compounds included derivatives of quinic acid, O-glycosylated flavonoids, a caffeic acid derivative and a protocatechuic acid derivative. The characteristic loss of 206 Da from malonylcaffeoyl quinic acid was used to confirm the malonyl linkage to the caffeoyl group. This contribution presents one of the first reports on the analysis of phenolic compounds from Helichrysum devium using LC-DAD/ESI-MS(n) and highlights the prominence of quinic acid derivatives as the main group of phenolic compounds present in these extracts. We also provide evidence that the methanolic extract from the flowers was significantly more complex when compared to that of other morphological parts.